Comparative Expression Profiles of Midgut Genes in Dengue Virus Refractory and Susceptible Aedes aegypti across Critical Period for Virus Infection - Chauhan, Chitra; Behura, Susanta K.; deBruyn, Becky; Lovin, Diane D.; Harker, Brent W.; Gomez-Machorro, Consuelo; Mori, Akio; Romero-Severson, Jeanne; Severson, David W. (PLOS ONE, 2012)
Background Aedes aegypti is the primary mosquito vector for dengue virus (DENV) worldwide. Infectivity of dengue virus varies among natural populations of this mosquito. How A. aegypti responds to DENV infection relative to which genes and associated pathways contribute to its differential susceptibility as a vector is not well defined. Methods/Principal Findings Here, we used custom cDNA microarrays to identify groups of genes that were differentially expressed in midgut tissues between susceptible and refractory strains in a highly time specific manner. While genes involved in protein processing in the endoplasmic reticulum, mRNA surveillance, and the proteasome were significantly up-regulated in the susceptible strain, several metabolic processes including glycolysis, glycan biosynthesis and Wnt pathway were active in the refractory strain. In addition, several key signaling genes were expressed as common responsive genes in both susceptible and refractory mosquitoes that may be necessary for signal transduction to trigger the appropriate host response to the viral infection. These are coordinately expressed in the form of tight gene networks and expression clusters that may be necessary to differentially contribute to the progression of dengue infection between the two strains. Conclusions Our data show that highly correlated differential expression of responsive genes throughout the post infection period in A. aegypti midgut tissues is necessary for a coordinated transcriptional response of the mosquito genes to host or defend the viral infection.